2020
DOI: 10.1177/0269881120965892
|View full text |Cite
|
Sign up to set email alerts
|

Effects of caffeine on ethanol-elicited place preference, place aversion and ERK phosphorylation in CD-1 mice

Abstract: Background: Epidemiological studies indicate a rise in the combined consumption of caffeinated and alcoholic beverages, which can lead to increased risk of alcoholic-beverage overconsumption. However, the effects of the combination of caffeine and ethanol in animal models related to aspects of drug addiction are still underexplored. Aims: To characterize the pharmacological interaction between caffeine and ethanol and establish if caffeine can affect the ability of ethanol (2 g/kg) to elicit conditioned place … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 66 publications
3
13
0
Order By: Relevance
“…Interestingly, in the present study using mice, EtOH (1.5 g/kg) significantly induced pERK, and this effect was counteracted by caffeine at both doses in both AcbC and AcbSh. These results are consistent with a recent paper from our laboratory in which caffeine (3 and 15 mg/kg) blocked EtOH (2.0 g/kg) induction of pERK in both subregions of Acb as well as 2 nuclei in the amygdala in this same strain of mice (Porru et al, 2020).…”
Section: Discussionsupporting
confidence: 93%
“…Interestingly, in the present study using mice, EtOH (1.5 g/kg) significantly induced pERK, and this effect was counteracted by caffeine at both doses in both AcbC and AcbSh. These results are consistent with a recent paper from our laboratory in which caffeine (3 and 15 mg/kg) blocked EtOH (2.0 g/kg) induction of pERK in both subregions of Acb as well as 2 nuclei in the amygdala in this same strain of mice (Porru et al, 2020).…”
Section: Discussionsupporting
confidence: 93%
“…The results of the present study also confirm that both ethanol (Porru et al 2020(Porru et al , 2021Rosas et al 2017) and morphine (Rosas et al 2016;Valjent et al 2004) activate ERKs phosphorylation in the AcbSh of CD1 mice and show for the first time that both WSE (50 mg/kg) and DF (2 mg/ kg) are able to prevent these increases. The acute effects of WSE and DF in the prevention of either ethanol-or morphine-induced ERKs phosphorylation in the AcbSh was assessed, in distinct cohorts of animals, to better define the molecular mechanisms leading to WSE's and DF's prevention of the acquisition of ethanol-or morphine-elicited CPP.…”
Section: Discussionsupporting
confidence: 87%
“…Post-hoc analysis using the Newman-Keuls test confirmed that EtOH increases the number of AcbSh pERK-positive neurons (Ibba et al 2009;Porru et al 2020) and showed that pre-treatment with DF prevents this effect (p < 0.05). Figure 4B shows the effects of pre-treatment with vehicle (Veh) or DF (2 mg/kg) 30 min before the administration of vehicle (Veh) or morphine (MOR, 5 mg/kg) on the number of pERK-positive neurons in the AcbSh.…”
Section: Effects Of Df On Ethanol-and Morphine-induced Erk Phosphorylation In Acbshmentioning
confidence: 86%
See 2 more Smart Citations